2020
DOI: 10.5455/javar.2020.g444
|View full text |Cite
|
Sign up to set email alerts
|

The effect of facial hair whorl position and raising environment on the temperament of the Chinese Yellow cattle in Shinjang Uyghur Aptonom Rayoni, China

Abstract: Objective: The objective of this study is to determine whether there is a relationship between hair whorl position and temperament in Chinese Yellow cattle using a questionnaire. Also, the effect of the raising environment is investigated. Materials and methods: A total of 122 Chinese Yellow cattle were surveyed in 3 village areas and four grassland areas in the northern area of China. For each cattle, an investigator asked the care-person about each item of a temperame… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…Broucek et al (2004) reports an association of hair whorl position and learning ability and locomotor behaviour in cattle. Aierqing et al (2020) found a relationship between the location of the hair whorl and the animal's adaptability, obedience, and excitability. Couse (2015) reports that bulls with a round hair whorl between their eyes are more likely to produce high quality sperm than bulls without the same.…”
Section: Resultsmentioning
confidence: 96%
“…Broucek et al (2004) reports an association of hair whorl position and learning ability and locomotor behaviour in cattle. Aierqing et al (2020) found a relationship between the location of the hair whorl and the animal's adaptability, obedience, and excitability. Couse (2015) reports that bulls with a round hair whorl between their eyes are more likely to produce high quality sperm than bulls without the same.…”
Section: Resultsmentioning
confidence: 96%